Lepidoptera de santa maria e arredores. II. Sphingidae - Carvalho, Solon; Tarragó, Manoel Fernando S.; Biezanko, Ceslau Mário; Link, Dionísio (Revista do Centro de Ciências Rurais, 2008)
Em Santa Maria e arredores foram constatadas 42 espécies de Sphingidae . São referidos dados sobre hábitos dos adultos e larvas, plantas hospedeiras e inimigos naturais. Abstract Fourty two species of Sphingidae were found to occur at Santa Maria and neighboring regions, Rio Grande do Sul, Brazil. Data were collected on the habits of adults and larvae, host plants and natural enemies were noted when known.